ปัจจัยที่สัมพันธ์กับคุณภาพการนอนหลับของผู้ป่วยวัยผู้ใหญ่ : การวิเคราะห์อภิมาน - มธุรส กัลหโสภา (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purposes of this meta-analysis were to study the relationship between some particular factors and sleep quality in adult patients. 11 samples of correlational research documents that published in B.E. 1993-2007 were included. To synthesize those, 11 research characteristic variables were gathered by employing research characteristic coding form and research quality evaluation form. Then the Glass, McGaw, & Smith (1981) method was employed to synthesize all variables for correlation coefficients. There were 140 correlation coefficients, 86 correlation coefficients of personal factors (1.individual, 2.symptom, 3.signs, 4.mood, 5.behavior), 24 correlation coefficients of environment factors (1.noise, 2.light, 3.temperature, 4.interior condition, 5.unfamiliar environment), 30 correlation coefficients of general factors (1.discomfort, 2.nightmare, 3.nursing activity, 4.sleep disturbance). The result of research synthesis were: 1. The majority of the study were Master theses (90.9%). Most of instruments were tested for both reliability and validity; decided in very good quality. 2. The factor indicating the highest related to sleep in adult patients was the general factors ( r =.230 ), followed by personal factors ( r = .194 ) there were The factors indicating the least related to sleep in adult patients was environment factors ( r = .188 ) 3. The general factors had the large effect–size ( d = .496), the personal factors and environment factors had the medium effect-size on sleep quality ( d = .499, .430) 4. The research finding indicated that large effect–size was the general factors consisted of 4 sub-factors , there were sleep disturbance factors and discomfrot factors had the large effect–size ( d = .93, .60)